Enhancing Livelihoods: Mushroom Cultivation Practices and Challenges of Smallholder Farmers in Svay Rieng and Svay Chrum Districts, Cambodia - Chanthan Or; Putheasath Sin; Chhun Hong; Vanchey Ros; Tithya Kang; Dina Pen; Mardy Serey (PT. Altaf Publishing Corp, 2025)
Smallholder farmers in Svay Rieng Province, Cambodia, play a crucial role in the country's agricultural sector, particularly in mushroom cultivation. Despite facing numerous challenges such as limited access to resources, climate change, and market uncertainties, these farmers contribute significantly to the national food security. This study aims to explore the technical knowledge, technical adaptation and practices of mushroom growing, and to analyze the economic efficiency of mushroom growing of smallholder farmers in Svay Rieng and Svay Chrum districts, Svay Rieng province, Cambodia. Eight farmers in three target villages were selected for household surveys (four farmers were the target and others four are non-target). Two types of mushroom were selected to grow by farmers, which are Straw and Oyster Mushroom. Fifty percent of farmers (both target and non-target) experienced in mushroom growing for more than five years and all of target farmers received technical training on mushroom growing from HEQCIP Project while only half of the non-target farmers used to get training from Government project (Provincial Department of Agriculture). At the same time, only one half of interviewed farmers share their technical knowledge and experiences on mushroom growing with their relatives, neighbors, and other farmers in their communities. All farmers apply mushroom growing techniques provided by the project together with their experiences and local knowledge. Even farmers in the targeted communities used natural fertilizers in mushroom growing, but 50% of them still used chemical fertilizers. It is interesting that all farmers sprayed jungle white before start growing, except 25% of the straw mushroom targeted farmers do not do that. The average profits for a targeted farmer gained from mushroom growing per production cycle is 600,250 Riels which is equal to 180% compared with expenses; or 60% compare with the total incomes while the non-targeted farmers profit is about 110% (504,250 Riels) compared with the expense; or 50% compared with the incomes. Even though the profit percentage from mushroom growing is higher than vegetable cultivation, but only 25% of the target and 50% of the non-target farmers who indicated their livelihood have improved a lot while the rest mentioned little improvement. This is because 50% of targeted and 75% of non-targeted farmers used incomes from mushroom production to repay their loan.